Theoretical modeling and FEA simulation of a CMOS-MEMS resonator - Ahmed, A.Y. (Institute of Electrical and Electronics Engineers Inc., 2017)
Relative humidity sensing is crucial in many applications. However, hysteresis, lack of stability and low accuracy still exist in some of the available humidity sensors. This paper studies the effect of changing the supported beams' length and width on the resonance frequency and mass sensitivity of a CMOS-MEMS resonator proposed for relative humidity sensing applications. The resonator is designed based on 0.35 μm CMOS technology. The resonance frequency and mass sensitivity were found to be in a range of 6.195 kHz-17.852 kHz and 1.498 mHz/pg-4.301 mHz/pg, respectively, when the length of the beams was changed from 500 μm to 300 μm, while decreasing the beams' width was found to decrease the resonance frequency and subsequently the mass sensitivity. FEA simulation using 2008 CoventorWare software was used to confirm the analytical results, in which the analytical and simulation results of frequencies and mass sensitivities showed good agreement within a percentage error of 0.80 for both of them. © 2017 IEEE.